PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP HASIL BELAJAR KIMIA SISWA KELAS XI IPA 2 PADA POKOK BAHASAN LAJU REAKSI DI SMA NEGERI 1 KASIMBAR - Masrah, Masrah; Ratman, Ratman (Universitas Tadulako, 2013)
This sudy presents the research of classroom action (PTK) executed in two cycle, in which every cycle cover the planning, execution, observation and reflection. This research aims to increase chemistry result study for student of XI IPA2 class on senior high school 1 of Kasimbar in rate reaction material through application of cooperative learning two stay two stray model. Research subject was XI IPA2 class on senior high school 1 of Kasimbar amount to 35 students. Data type was collected data qualitatively in the form of result of observation of student activity and learn at the time of process learn take place, and quantitative data in the form of result learn the student of final tes evaluation of action. Result of cycle I obtained by activity of student and teacher be at the good criterion, percentage of absorpsion classical 62.0% and complete learn the classical 65.7%. The second cycle experience of the improvement, that is activity of student and teacher be at the criterion very good, percentage of absorpsion classical 76.8% and complete learn the classical 88.5%. Results indicated that the application cooperative learning model two stay two stray can improved chemistry result study for student of xi IPA2 class in reaction rate material on senior high school 1 of Kasimbar.